Comparative evaluation of Agricultural alternatives in the Province of Carchi - Ibarra Rosero , Edison Marcelo; Campos Vallejos , Rolando Martin; García Bolívar, Judith Josefina; Benavides Rosales , Hernán Rigoberto (Tierra Infinita, 2020)
This research was carried out in cooperation between the Universidad Politécnica Estatal del Carchi and the company TERRAFERTIL, with the aim of defining agricultural alternatives for the Carchi province. Three agricultural crops different from the traditional ones were considered, lemon verbena (Aloysia citriodora), lemon balm (Melissa officinalis), and golden berry (Physalis peruviana), all of them with the connotation of having an organic management. The lemon balm and golden berry crops were carried out in the open field at the San Francisco Experimental Center - UPEC, located in the Huaca canton, while the lemon verbena crop was implanted under cover (greenhouse) at the Alonso Tadeo Experimental Center - UPEC, located in La Concepción parish, Mira canton. The variables under study for medicinal crops (lemon verbena and lemon balm) were considered as the production of gross biomass (leaves and branches) and the benefit / cost ratio; for the golden berry crop, the production and the benefit / cost ratio were evaluated. With the analysis of the variables, it was obtained that the organic cultivation of lemon verbena is the one with the highest yield with 40.69 ton.ha-¹.year-¹. The crops with the highest production costs are golden berry, lemon verbena and potato respectively, unlike the lemon balm crop which is the one with the lowest cost. The lemon verbena and lemon balm crops are the crops with the best Benefit / Cost ratio (B / C) with values ​​of 2.78 and 2.71 respectively. It can be concluded from the present investigation that the best agricultural alternatives for the province of Carchi are organic crops of lemon verbena and lemon balm.